A polarization image enhancement method for glioma - Liu, Yi-Rong; Liang, Chao-Feng; Zhao, Han-Qiao; Ou, Yun-Mou; Wu, Jian (Frontiers in Neuroscience, 2023)
Polarization imaging technique (PIT) based on a backward scattering 3 × 3 Mueller matrix polarization imaging experimental setup is able to study the optical information and microstructure of glioma and non-glioblastoma tissues from clinical treatment. However, the image contrast of Mueller Matrix Elements (MME) is far from sufficient to provide supplemental information in the clinic, especially in off-diagonal MME. The aim of this work is to propose an innovative method to improve the contrast and quality of PIT images of glioma and non-glioma tissues. The work first confirms the robustness of the method by evaluating the enhanced images and assessment coefficients on ex vivo unstained glioma and non-glioma sample bulks, then the optimal enhancement results are tested and presented based on the multi-sample tests. This PIT image enhancement method can greatly improve the contrast and detailed texture information of MMEs images, which can provide more useful clinical information, and further be used to identify glioma and residues in the intraoperative environment with PIT.